Comparative Genomics of Aeromonas hydrophila Secretion Systems and Mutational Analysis of hcp1 and vgrG1 Genes From T6SS - Tekedar, Hasan C.; Abdelhamed, Hossam; Kumru, Salih; Blom, Jochen; Karsi, Attila; Lawrence, Mark L. (Frontiers in Microbiology, 2019)
Virulent Aeromonas hydrophila causes severe motile Aeromonas septicemia in warmwater fishes. In recent years, channel catfish farming in the U.S.A. and carp farming in China have been affected by virulent A. hydrophila, and genome comparisons revealed that these virulent A. hydrophila strains belong to the same clonal group. Bacterial secretion systems are often important virulence factors; in the current study, we investigated whether secretion systems contribute to the virulent phenotype of these strains. Thus, we conducted comparative secretion system analysis using 55 A. hydrophila genomes, including virulent A. hydrophila strains from U.S.A. and China. Interestingly, tight adherence (TaD) system is consistently encoded in all the vAh strains. The majority of U.S.A. isolates do not possess a complete type VI secretion system, but three core elements [tssD (hcp), tssH, and tssI (vgrG)] are encoded. On the other hand, Chinese isolates have a complete type VI secretion system operon. None of the virulent A. hydrophila isolates have a type III secretion system. Deletion of two genes encoding type VI secretion system proteins (hcp1 and vgrG1) from virulent A. hydrophila isolate ML09-119 reduced virulence 2.24-fold in catfish fingerlings compared to the parent strain ML09-119. By determining the distribution of genes encoding secretion systems in A. hydrophila strains, our study clarifies which systems may contribute to core A. hydrophila functions and which may contribute to more specialized adaptations such as virulence. Our study also clarifies the role of type VI secretion system in A. hydrophila virulence.